2002
DOI: 10.1002/mas.10034
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscopic aspects of radiobiological damage: Fragmentation induced by secondary low‐energy electrons

Abstract: Low-energy electrons (LEEs) are produced in large quantities in any type of material irradiated by high-energy particles. In biological media, these electrons can fragment molecules and lead to the formation of highly reactive radicals and ions. The results of recent experiments performed on biomolecular films bombarded with LEEs under ultra-high vacuum conditions are reviewed in the present article. The major type of experiments, which measure fragments produced in such films as a function of incident electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
167
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 225 publications
(170 citation statements)
references
References 72 publications
1
167
0
2
Order By: Relevance
“…The last decade has witnessed immense advances in our understanding of the effects of ionizing radiation on biological systems [1,2]. DNA as a genetic information carrier is the most important species, among cellular components, prone to damage by high energy photons.…”
Section: Dna Damage Induced By Low Energy Electronsmentioning
confidence: 99%
“…The last decade has witnessed immense advances in our understanding of the effects of ionizing radiation on biological systems [1,2]. DNA as a genetic information carrier is the most important species, among cellular components, prone to damage by high energy photons.…”
Section: Dna Damage Induced By Low Energy Electronsmentioning
confidence: 99%
“…13,14 Thus, in recent years much research interest has been focused on the fragmentation and modification of DNA by low energy electrons (LEEs). 15,16,17 In experiments, molecular solid films of DNA held under ultra high vacuum (UHV) were bombarded with LEEs. Below about 15 eV, LEEs were found to induce strand breaks in DNA essentially via the formation of transient anions located on specific DNA components.…”
Section: Introductionmentioning
confidence: 99%
“…15 However, it is now well established that the processes induced by electron impact on the bio-molecules are highly dependent on their environment. 16,18,19 To gain further knowledge of LEE-DNA interactions in biological systems, it is therefore important to perform LEE-DNA experiments under conditions closer to those in the cell.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies on phenomena involving low energy electrons (LEEs) have shown that these particles play a central role in determining the effects of ionizing radiation. Thus, in recent years much research interest has been focused on the fragmentation and modification of DNA by LEEs (Sanche, 2002(Sanche, , 2005. The initial experiments on LEE-DNA were performed on DNA molecules under dry high vacuum conditions (Sanche, 2009;Boudaïffa et al, 2000;Cai et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The initial experiments on LEE-DNA were performed on DNA molecules under dry high vacuum conditions (Sanche, 2009;Boudaïffa et al, 2000;Cai et al, 2005). However, the damaging effects of LEEs on the DNA molecule are known to be dependent on its environment (Sanche, 2002;Lehnert, 2008;Ptasińska and Sanche, 2007;Barilla and Lokajíček, 2000). Thus, to better understand the damaging effects of LEE on DNA, attempts have been made to perform LEE-irradiation experiments under conditions more closely approximating those found in the cell.…”
Section: Introductionmentioning
confidence: 99%